Marketing Research on Consumer Pull and Dealer Push of Branded TMT Bars - Sarala, K. S.; Paramesha, N. (Indian Journal of Marketing, 2009)
The paper entitled Marketing Research on Consumer Pull and Dealer Push of Branded TMT bars is aimed at exploring consumer pull and dealer push of branded TMT bars in concurrent with steel industry. The paper carries the details about what steel as a product, global overview of steel sector along with domestic steel industry journey since from 1907 and discusses how the steel industry evolved overtime through policy changes as well as reforms taken by the government pre liberalization and post liberalization period. The paper holds the details of objectives and as well as scope and significance of steel sector to the developing India.